2017
DOI: 10.1103/physrevb.95.195113
|View full text |Cite
|
Sign up to set email alerts
|

Extremely large nonsaturating magnetoresistance and ultrahigh mobility due to topological surface states in the metallic Bi2Te3 topological insulator

Abstract: Weak antilocalization (WAL) effects in Bi2Te3 single crystals have been investigated at high and low bulk charge carrier concentrations. At low charge carrier density the WAL curves scale with the normal component of the magnetic field, demonstrating the dominance of topological surface states in magnetoconductivity. At high charge carrier density the WAL curves scale with neither the applied field nor its normal component, implying a mixture of bulk and surface conduction. WAL due to topological surface state… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
53
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 31 publications
13
53
1
Order By: Relevance
“…It is known that a sharp magnetoresistance dip at low temperatures indicates the presence of a WAL effect; when we increase the temperature, the magnetoresistance dip broadens at the low field due to the decrease of the phase coherence length at higher temperatures 48 . Similar types of magnetoresistance behavior without any sign of saturation have been seen in topological materials [48][49][50] . In particular, Shrestha et al 49 have recently shown extremely large nonsaturating magnetoresistance (540% at T = 2 K under 7 T) and ultrahigh Hall mobility (4.5 × 10 4 cm 2 V −1 s −1 at T = 5 K) due to topological surface states in the metallic Bi 2 Te 3 topological insulator 49 , results which are comparable with those of magnetoresistance ≈ 650% at 2.5 K under 6 T and Hall mobility ≈ 3.5 × 10 3 cm 2 V −1 s −1 at T = 2.5 K observed on our AuSn 4 single crystals (for details, see Supplementary Note 3).…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…It is known that a sharp magnetoresistance dip at low temperatures indicates the presence of a WAL effect; when we increase the temperature, the magnetoresistance dip broadens at the low field due to the decrease of the phase coherence length at higher temperatures 48 . Similar types of magnetoresistance behavior without any sign of saturation have been seen in topological materials [48][49][50] . In particular, Shrestha et al 49 have recently shown extremely large nonsaturating magnetoresistance (540% at T = 2 K under 7 T) and ultrahigh Hall mobility (4.5 × 10 4 cm 2 V −1 s −1 at T = 5 K) due to topological surface states in the metallic Bi 2 Te 3 topological insulator 49 , results which are comparable with those of magnetoresistance ≈ 650% at 2.5 K under 6 T and Hall mobility ≈ 3.5 × 10 3 cm 2 V −1 s −1 at T = 2.5 K observed on our AuSn 4 single crystals (for details, see Supplementary Note 3).…”
Section: Resultssupporting
confidence: 72%
“…Similar types of magnetoresistance behavior without any sign of saturation have been seen in topological materials [48][49][50] . In particular, Shrestha et al 49 have recently shown extremely large nonsaturating magnetoresistance (540% at T = 2 K under 7 T) and ultrahigh Hall mobility (4.5 × 10 4 cm 2 V −1 s −1 at T = 5 K) due to topological surface states in the metallic Bi 2 Te 3 topological insulator 49 , results which are comparable with those of magnetoresistance ≈ 650% at 2.5 K under 6 T and Hall mobility ≈ 3.5 × 10 3 cm 2 V −1 s −1 at T = 2.5 K observed on our AuSn 4 single crystals (for details, see Supplementary Note 3). We may also note that, due to the non-negligible contribution of transverse resistivity, as arising from the high Hall mobility, the original experimental resistivity data were asymmetric in the field.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Experimentally, the SS in topological insulators can be determined by Scanning Tunneling Microscopy (STM) and Angle-Resolved Photoemission Spectroscopy (ARPES) [5,17,18]. Numerous bismuth (Bi)-based materials such as Bi 1−x Sb x , Bi 2 Te 3, and Bi 2 Se 3 have been experimentally verified to possess these topological SS [19,20], and their existence in these 3D binaries TIs has been verified through magneto-transport measurements in thin films [21], and single crystals [22]. The surface states of these topological insulators, i.e., Bi 2 Te 3 and Bi 2 Se 3, are verified to possess only one helical Dirac cone [4,5,18], and WAL is intrinsic to them.…”
Section: Introductionmentioning
confidence: 99%
“…Our results indicate that LMR (linear magnetoresitance) observed at high temp range (>2K) is not sufficient for accessing the TSS and measurements at ultra low temp give more access to TSS. In the literature, MR measurements showing WAL effects were heavily used to prove the transport through TSS 13,14,19,[29][30][31] .…”
Section: Introductionmentioning
confidence: 99%